The World of Bullying: An Overview and Reflexion - Gerard Martinez-Criado (Coolabah, 2014)
The issue of bullying is of growing concern in developed countries. Considerable effort has been carried out to understand the problem and implementation programs have been launched to deal with this issue. In this paper we aim to define the concept of bullying and to present some data in relation to causes of bullying which have been highlighted by different researchers around the world. We aim to shed some light on the question of how to fight against bullying. Our conclusions stress the difficulties in conceptualising and researching bullying derived from cultural/social factors and from factors that relate to adolescence as a transitional and vulnerable period in life.